Analisis Kebutuhan Pengembangan E-Modul Matematika Berbasis Etnomatematika untuk Siswa Kelas IV Sekolah Dasar - Ni Ketut Diah Damayanti; I Putu Suardipa; I Komang Wahyu Wiguna (Jayapangus Press, 2026)
The low attainment of mathematics learning outcomes in elementary schools indicates the need for teaching materials that are contextual, systematic, and aligned with students’ developmental characteristics. This study aimed to analyze the need for developing an ethnomathematics-based mathematics e-module for fourth-grade elementary school students at the school-cluster level. This research was conducted as the initial stage of a development study using a descriptive quantitative and qualitative approach. The study involved seven schools in Cluster 1 of Kediri District, namely SDN 1 Kaba-Kaba, SDN 2 Kaba-Kaba, SDN 4 Kaba-Kaba, SDN 2 Buwit, SDN 1 Cepaka, SDN 1 Nyambu, and SDN 2 Nyambu. Data were collected through observation, interviews, and document analysis, and were analyzed descriptively. The findings showed that students’ attainment of mathematics learning outcomes ranged from 45% to 58%, with a cluster average of 52.14%. These results indicate an empirical need for a mathematics e-module that is not merely digital but also capable of connecting concepts of numbers, fractions, measurement, geometry, and data representation with Balinese local cultural contexts. The main contribution of this study lies in mapping the development needs for an ethnomathematics-based mathematics e-module at the elementary school-cluster level as an initial basis for product design. Therefore, an ethnomathematics-based e-module is feasible to be developed as an alternative teaching material that is more concrete, meaningful, and relevant to students’ learning experiences.